If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -17 = -50 Reorder the terms: -17 + 3x = -50 Solving -17 + 3x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 3x = -50 + 17 Combine like terms: -17 + 17 = 0 0 + 3x = -50 + 17 3x = -50 + 17 Combine like terms: -50 + 17 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| y=-3cosx+2sinx | | 6x-6+4x=3 | | 2x-x+5(x+4x)-8-9=20 | | 2x-5x+5(x+4x)-8-9=20 | | 4x*5x=270 | | 17-9+4+6x=19 | | 4x-5(2x+5)=4(x+3) | | 4/3•64 | | 5x-4+-2x+3=-7+-3x+5+2x | | 8x+2x+30=180 | | (2x+y)dx+(x+6y)dy=0 | | -6+4=92 | | -8x+5x+8=10 | | 2q-29=q+16 | | 6-4=92 | | -57+x=63-9x | | y=4/7x=2 | | x+3+x+5= | | b-50=8 | | 2b^2-b-28=0 | | q+23=24q | | 7a+47=25a-25 | | 9b^2-38b+8=0 | | x(0.10)=7194-x | | 4+6(-6-4x)=92 | | 3c=c+44 | | 15.12(x-5)=30 | | 19w-45=4w | | 9y-7=8y | | 3x+5x-2x+18=42 | | x+2(3)=2 | | x(0.06)=6996-x |